A fundamental investigation on supercritical carbon dioxide energetic, exergetic and entropy behavior in parabolic trough solar collector. (15th January 2023) - Zaharil, Hafiz Aman; Yang, Hongxing
Abstract: Supercritical carbon dioxide (s-C O 2 ) has been gaining prominence among researchers due to its ability to operate at high temperatures and overcome the current state-of-the-art parabolic trough solar collector system's limitation. This research aims to investigate the energetic, exergetic and entropy performance of the PTSC under a wide range of operating and climatic conditions in detail. Using a modified LS-3 PTSC as a model, a 1-D mathematical model was validated with previous works and solved by using EES under a steady-state condition. The results showed that the system's primary energy efficiency is greatly affected by pumping power requirement while the impact is less prominent on exergetic efficiency. When the system was tested under actual climatic conditions, its energetic performance showed consistent results with fixed conditions, but contrary results were observed for exergetic efficiency. The most important observation was that the performance of Tin = 550K noticeably outperformed Tin = 750K & 850K, which contradicted previous studies with fixed climatic conditions. Besides that, at low DNI levels, the results showed that s-C O 2 's primary thermal and exergetic performance at high temperatures (750K & 850K) was greatly reduced. For entropy analysis, the dominant reason for entropy generation is primarily due to exergy destruction for the two most important inlet temperatures (550K & 650K). The overwhelming reason for entropy generated due to exergy destruction is between the sun and the receiver with a ratio of ≥ 95 % . Whereas the dominant cause of exergy loss is primarily due to optical loss. Highlights: The fundamental analysis of supercritical CO2 in parabolic trough were done in detail. Pumping power has substantial influence on the overall efficiency. DNI and inlet temperature has great impact on overall and exergetic efficiency. The dominant reason for entropy generation is primarily due to exergy destruction. Detailed discussion of exergy destruction and exergy loss were done.